Electron Trap Dynamics in Polymer Light‐Emitting Diodes. (10th April 2022) - Diethelm, Matthias; Bauer, Michael; Hu, Wei‐Hsu; Vael, Camilla; Jenatsch, Sandra; Blom, Paul W. M.; Nüesch, Frank; Hany, Roland
Abstract: Semiconducting polymers are being studied intensively for optoelectronic device applications, including solution‐processed light‐emitting diodes (PLEDs). Charge traps in polymers limit the charge transport and thus the PLED efficiency. It is firmly established that electron transport is hindered by the presence of the universal electron trap density, whereas hole trap formation governs the long‐term degradation of PLEDs. Here, the response of PLEDs to electrical driving and breaks covering the timescale from microseconds to (a few) hours is studied, thus focusing on electron traps. As reference polymer, a phenyl‐substituted poly( para ‐phenylene vinylene) (PPV) copolymer termed super yellow (SY) is used. Three different traps with depths between ≈0.4 and 0.7 eV, and a total trap site density of ≈2 × 10 17  cm −3 are identified. Surprisingly, filling of deep traps takes minutes to hours, at odds with the common notion that charge trapping is complete after a few hundred microseconds. The slow trap filling feature for PLEDs is confirmed using poly(2‐methoxy‐5‐(2‐ethylhexyloxy)‐1, 4‐phenylene vinylene (MEH‐PPV) and poly(3‐hexylthiophene) (P3HT) as active materials. This unusual phenomenon is explained with trap deactivation upon detrapping and slow trap reactivation. The results provide useful insight to pinpoint the chemical nature of the universal electron traps in semiconducting polymers. Abstract : The filling of deep electron traps for a range of polymer‐based light‐emitting diodes needs many minutes, in contrast to the general notion that trap filling is completed after hundreds of microseconds. This remarkable appearance is consistent with a slow diffusion process between precursor trap species that form a trap only while meeting with the hydrated oxygen complex as a possible candidate.